PEMBERIAN URIN SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Riadhos Sholikhin; Nurbaiti '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the effectiveness and get the best concentration of cow urine on the growth and yield of mustard (Brassica juncea L.). This research was conducted at the experimental station Faculty of Agriculture, University of Riau in January to February 2014. Completely Randomized Design with 5 treatments and 4 replications use in this experiment. The treatment consisted application of cow urine with concentrations is : U0 : without application of cow urine, U1: 14 cc/l of water, U2 : 19 cc/l of water, U3 : 24 cc/l of water and U4 : 29 cc/l of water. Data were analyzed using analysis of variance and mean separations with Duncan Multiple Range Test at the 5% level. The Parameters measured were the plant height, leaf number, leaf area, root volume, plant fresh weight and weight of crop suitable for consumption. The results showed that application of cow urine is significantly affected to parameters of plant height, leaf number, leaf area, root volume, plant fresh weight and weight of crop suitable for consumption. Application of cow urine at concentrations of 29 cc/l of water is the best concentration for all parameters tested. Keyword : Cow Urine, Mustard, Growth, Yield